Indirect Genetic Effects on Male Territoriality in Drosophila melanogaster - Ducharme, Tristan (Université d'Ottawa / University of Ottawa, 2022)
When an individual interacts socially with a conspecific, their behavioural phenotype is affected directly by their genotype (‘direct genetic effect’, DGE), but may also be affected indirectly by the genotype of the opposing individual (‘indirect genetic effect’, IGE). While there is no doubt that IGEs occur in various organisms and contexts, it is unknown how properties of the environment may influence the relative magnitude of DGEs, IGEs, and their covariance. To gain insight into this, I examined territorial interactions in Drosophila melanogaster. Due to their short generation time and relatively simple care requirements, D. melanogaster has been used extensively in quantitative genetic research. Using offspring from a half-sib breeding design, I constructed an arena for documenting multiple dyadic territoriality assays with two sizes of a food resource. With this apparatus, 618 territoriality contests between 1,236 individuals were recorded and scored for four key aggressive behaviours. The results revealed significant genetic variation in how opponent effects on focal individuals changed between environments (i.e., genetic variation in the plasticity of IGEs). In addition, changes in DGEs and IGEs between environments were strongly and positively correlated (i.e., there was a DGE × IGE × environment interaction), although confirmation of this result in further studies is warranted because it was non-significant (P = 0.10), likely due to large uncertainties arising in part from some small variance component estimates. As a high throughput system for quantify IGEs in territoriality in Drosophila, my approach holds promise but there are issues to resolve, including automating phenotyping behaviors in place of manual scoring to enable many more trials. Additionally, modifications to increase humidity during trials might result in increased expression of certain territorial behaviours.
Keywords: Indirect Genetic Effects; Quantitative Genetics